Effect of Emotional Experience, Electronic Word of Mouth, Reputation, Customer Satisfaction on Loyalty - Brendi Wijaya; Henilia Yulita (Ilomata International Journal of Management, 2020)
Lion Air was chosen by the public as an airline because of its lower fares compared to other airlines. However, Lion Air also often creates problems in terms of service, namely passenger displacement due to delay. With a negative emotional experience will have an effect on reputation decline, due to electronic word of mouth by consumers who are dissatisfied with the service. This type of research uses quantitative methods. The population of this research is all consumers who have used Lion Air transportation services with a sample of 100 respondents. The data collection method uses purposive sampling method. Technical analysis using SMART PLS 3.0 consists of three types, namely instrument testing, prerequisite tests, and hypothesis testing. The results showed that consumer satisfaction is influenced by emotional experience, E-Wom is influenced by emotional experience, reputation is not influenced by emotional experience, loyalty is not influenced by customer satisfaction, E-Wom is influenced by customer satisfaction, reputation is influenced by consumer satisfaction, Loyalty is influenced by Reputation, Reputation is influenced by E-Wom, and Loyalty is also influenced by E-Wom.